UPAYA KEPEMIMPINAN KEPALA DESA DALAM MENINGKATKAN PROFESIONALISME KERJA APARATUR DI KANTOR DESA SIPODECENG - Muh Ali Akbar Darlis; Suranto Suranto; Salmawati Salmawati (FISIP Universitas Muhammadiyah Sidenreng Rappang, 2023)
This study aims to determine the efforts of village heads in increasing the professionalism of apparatus work at the Sipododeceng village office. The population in this study amounted to 38 people. Sampling was carried out with a total sample, namely taking the entire population so that it became 38 people. The data collection techniques used in this study were observation, interviews, literature review and questionnaires. The collected data is then used by means of quantitative analysis techniques with frequency tables. The results showed that the village head's efforts to improve the professionalism of the apparatus at the Sipodeceng Village Office were categorized as good with a percentage of 71%. Cooperation motivation is the most dominant value. Cooperation motivation is a condition that influences to generate, direct, and maintain behavior related to the work environment. The professionalism of the work of the apparatus in the Sipodeceng Village Office, Baranti District, Sidenreng Rappang Regency is cooperation in commitment with a percentage of 73.5%. The most dominant value is the accountability of apparatus at work when they make mistakes serving the community and the influence of transformational leadership on increasing the professionalism of apparatus work at the Sipodeceng Village Office, Baranti District, Sidenreng Rappang Regency is categorized as influential with a percentage of 72%. The most influential indicator is motivation.